Hegemonic femininity in Tamil movies: exploring the voices of youths in Chennai, India. Issue 1 (2nd January 2016) - Karupiah, Premalatha
Abstract : The media often showcase culturally normative forms of masculinity and femininity. This paper explores the portrayal of femininity in Tamil movies and examines the youths' views on these portrayals. The data for this paper came from a content analysis of 40 movies (1961–2012) and 30 face-to-face interviews with undergraduates in Chennai, India. Women's roles in Tamil movies can be regarded as secondary in nature, and meant for the male gaze. These roles emphasize traditional feminine ideals. Tamil movies are cautious about challenging the deeply rooted traditional feminine ideals of Tamil society. The strong maintenance of traditional femininity is one of the reasons why it is seen as a form of hegemonic femininity: that is, a form of femininity that holds ascendancy when compared to other forms of femininity. Youths sometimes question the stereotypical portrayal of women, but are not always able to resist them.